PENGUATAN LITERASI LINGKUNGAN SISWA MELALUI SEKOLAH BEBAS SAMPAH BERBASIS 5R DI SMP UNISMUH MAKASSAR - Fatmawati A. Mappasere; Ratna Dewi; Abd. Hadi Aqsha; J Julianti (LPPM Universitas Nusa Mandiri, 2026)
Urban waste generation continues to increase, and a substantial portion remains unmanaged, making education and the habituation of waste management practices from the school level a strategic necessity. At SMP Unismuh Makassar, daily waste generation is estimated at 15–20 kg; however, its management has not yet been supported by standard operating procedures (SOPs) or adequate waste-sorting facilities. This Community Service Program, entitled Waste-Free School, aimed to strengthen the environmental literacy of the school community and improve school waste management governance based on the 5R principles (Refuse, Reduce, Reuse, Recycle, dan Rot). The program consisted of environmental literacy education, technical training on waste sorting and processing through composting and the school waste bank, provision of supporting facilities such as sorting bins and composters, institutional strengthening of the school waste bank, and monitoring and evaluation. Program effectiveness was assessed using pre-tests, post-tests, and observation, and the data were analyzed using descriptive statistics, gain scores, and normalized gain (N-gain). The results showed that the students’ mean understanding score increased from 29.52 to 38.12, with an average gain of 8.60 points or 29.1%. A total of 84% of students achieved a moderate to high N-gain category, indicating that the program effectively improved students’ understanding of the 5R concept and began to foster waste-sorting practices at school. This program has the potential to be replicated in similar schools through integration into the School Work Plan (RKS) and continued institutional strengthening.